RESEARCH ON CHANGES IN THE GLOBAL COMPETITIVENESS LATVIA IN 2009-2019 - Volkova, Jeļena; Višķers, Ēvalds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In the era of globalization the term competitiveness has become of essential importance. Each country is showing its interest in it because the results of national economic processes depend on its successful alignment with the international market. The aim of this research is to define the changes in the Latvia’s Competitiveness Index in comparison with the Baltic States during the period 2009-2019. To achieve this aim the following methodology was used: scientific inductive and deductive methods,the monographic and the data based method. The research is based on the results of the assessement of the „Global Competitiveness Index”introduced by the World Economic Forum. Regardless of the methodological drawbacks and changes, the GCI states the status of Estonia as an economic leader among the Baltic States. The tendency seen in the last years shows the levelling of the competitiveness of the Baltic States that can have a positive impact on the development of the region in the further period.